Treatment strategies for chemotherapy-induced peripheral neuropathy: potential role of exercise - Karen Y. Wonders; Beverly S. Reigle; Daniel G. Drury (Frontiers Media S.A., 2011)
Chemotherapy-induced peripheral neuropathy (CIPN) is a common, dose-limiting effect of cancer therapy that often has negative implications on a patient's quality of life. The pain associated with CIPN has long been recognized as one of the most difficult types of pain to treat. Historically, much effort has been made to explore pharmacological therapies aimed at reducing symptoms of CIPN. While many of these agents provide a modest relief in the symptoms of peripheral neuropathy, many have been shown to have additional negative side effects for cancer patients. Therefore, the authors suggest exercise rehabilitation as one lifestyle modification that may positively impact the lives of patients with CIPN. To our knowledge, there are currently no published clinical trials examining the role of exercise in preserving neurological function following chemotherapy. However, investigations using low-to-moderate intensity exercise as an intervention in patients with diabetic peripheral neuropathy and hereditary motor and sensory neuropathies have produced promising results. Given that cancer patients appear to tolerate exercise, it seems plausible that exercise rehabilitation could be used as an effective strategy to minimize CIPN-induced detriments to quality of life.